2017
DOI: 10.1097/wnp.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

The Percentage of Amplitude Decrease Warning Criteria for Transcranial MEP Monitoring

Abstract: Muscle motor evoked potentials (MEPs) from transcranial electrical stimulation (TES) became a standard technique for monitoring the motor functions of the brain and spinal cord at risk during spinal and brain surgery. However, a wide range of criteria based on the percentage of amplitude decrease is used in practice. A survey of the current literature on clinical outcome parameters reveals a variety of percentages in a range of 30% to 100% (50% to 100% spinal procedures) with no consensus. The interpretation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 46 publications
0
21
1
Order By: Relevance
“…The trial-to-trial variability of amplitudes varies for TES between 1:1.3 and 1:6.5, and variations between 1:1.4 and 1:13 are observed for TMS. These values are somewhat higher than those reported in anesthetized human patients for stimulation intensities at supramaximal levels (range is 1:1.7 to 1:3.3) and are lower than the large variation of 1:26 at intensities just above ET ( Journée et al, 2017 ). The amplitude variations at supra-maximum intensity agree with those reported in a previous study ( Journée et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 63%
“…The trial-to-trial variability of amplitudes varies for TES between 1:1.3 and 1:6.5, and variations between 1:1.4 and 1:13 are observed for TMS. These values are somewhat higher than those reported in anesthetized human patients for stimulation intensities at supramaximal levels (range is 1:1.7 to 1:3.3) and are lower than the large variation of 1:26 at intensities just above ET ( Journée et al, 2017 ). The amplitude variations at supra-maximum intensity agree with those reported in a previous study ( Journée et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 63%
“…Even though this finding were not reproduced in the substudy 2, a possible explanation could be the small sample size of the study. As has been previously described, 38‐40 tcMEP amplitude and morphology vary from trace to trace due to the mechanism of MEP generation and, moreover, there is considerable inter‐ and intra‐individual variability in patients under general anaesthesia 8 . The generation of tcMEPs requires synaptic transmission at the anterior horn cell, which is facilitated by a train of stimulus pulses 41 .…”
Section: Discussionmentioning
confidence: 96%
“…Thus, the preoperative nTMS risk stratification not only correlates with MEP amplitude alterations but also provides information that can improve the interpretation of IOM findings, especially for identifying false-positive amplitude changes. This is particularly important because recent studies have reported various neurosurgical as well as anesthesiologic causes that may affect MEP amplitude and could not be distinguished from phenomena induced by direct tissue lesions (39,(42)(43)(44). To our knowledge, our analysis is the first one that can help to distinguish true-positive from false-positive MEP amplitude alterations.…”
Section: Iom -Transcranial Mep Monitoringmentioning
confidence: 94%